Recontextualizing internationalization of higher education institutions in South Korea through the lens of the knowledge-policy-power interface - Minjeong Jeon; Yoonjung Hwang; Moon Suk Hong (Emerald Publishing, 2023)
Purpose - This paper aims to critically investigate the past hype of internationalization of higher education institutions (HEIs) and its complex international, national and local processes under the influence of globalization. Design/methodology/approach - In particular, the authors employed the knowledge-policy-power interface framework through a scoping review in order to reexamine the political dynamics among international, national and local higher education actors in driving the internationalization of HEIs in the context of South Korea between the 1990s and the 2020s. The perspective taken by this research brings much-needed nuance to the analysis by focusing on the complex dynamics of external factors and key actors and their responses in the process of internationalization. Findings - This research found three characteristic dynamics of internationalization of Korean HEIs: uncritical acceptance of external pressures for internationalization; unbalanced formal and informal participation at the national level and different ways HEIs absorb change. In short, this research discussed how the powerful government, which has been stirred by external forces, shaped the limited knowledge discourse on internationalization while triggering power games among various HEIs. The research highlights that the characteristics of HEIs and the voices of all stakeholders should be better accounted for so that internationalization can proceed in diverse ways from the ground up to enhance and assure educational quality. Research limitations/implications - The research limits itself by analyzing the political dynamics in driving the internationalization of HEIs in the context of South Korea only through scoping review. However, the attempt to disentangle the underlying political dynamics through its original framework is worthy unlike previous more traditional models that cast policy-making as a uniform cycle proceeding rationally through the policy process regardless of the issue. Practical implications - These findings enable a better analysis of the key dynamics of how HEI internationalization policies in Korea were understood, planned and implemented. Without examining the political dynamics among various factors as well as the responses of significant actors to HEI internationalization, the current challenges and remaining tasks in translating higher education policy into practice cannot be thoroughly assessed. Social implications - Most importantly, the multilayered political dynamics that come together to shape the content and directions of policies in a certain national context should be taken into account in the process of policy-making. Such recontextualization would provide a better understanding of the underlying dynamics that lead to certain consequences of and challenges in translating higher education policy into practice, especially for those who face the challenge of balancing between state-driven policies and ever-diversifying needs and demands of HEIs. Originality/value - As there is a lack of understanding of the critical context of the knowledge-policy-power interface despite the significant influence of political dynamics in the process of internationalization, this research reexamined the internationalization of HEIs in Korea by providing a better understanding of the political dynamics between knowledge and power that influence the directions and contents of policy dialogues and documents.